Innovative Training in Learning Evaluation: Enhancing The Accuracy and Objectivity of Assessment in Elementary School (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Accurate and objective learning evaluation is essential for improving the quality of primary education. In Tasikmalaya City, many teachers still face difficulties in constructing valid, data-driven instruments that reflect authentic assessment principles. To address this challenge, a community service program was implemented to strengthen teachers’ capacity in designing and applying reliable evaluation tools. The initiative involved 45 elementary school teachers from the Nagarawangi Elementary School Complex in Tasikmalaya City and employed a structured method consisting of planning, interactive practice-based workshops, and evaluation of participants’ outputs. Training was conducted collaboratively and contextually, tailored to the characteristics of the teachers and the conditions of their schools. Descriptive data analysis was used to measure improvements in participants’ understanding and skills. Results indicate that 82% of teachers demonstrated enhanced competence in developing accurate and objective assessments, accompanied by the emergence of collaborative networks for co-developing sustainable evaluation systems. This initiative contributes uniquely by providing a replicable model of teacher empowerment that integrates professional development with practical classroom needs. The availability of reliable evaluation instruments not only supports continuous use in primary schools but also represents a foundational step in strengthening teacher capacity. Ultimately, the program aligns with and advances SDGs Goal 4 by promoting equitable, high-quality education through improved assessment practices.